Big data processing with Hadoop - Revathi, T.; Muneeswaran, K.; Pepsi, M. Blessa Binolin (Advances in data mining and database management (ADMDM) book series, 2019)
This book outlines the overview of the Big data. It presents the big data components organized as four layers such as: big data sources, data massaging and store layer, analysis layer, and consumption layer. It also gives a detailed knowledge of Hadoop platform.